Maraknya Usaha Franchise dalam Perspektif Field dan Habitus : (Studi Kasus Tren Perdagangan Es Teh Solo) - Ciek Julyati Hisyam; Aryo Anargya Hakim Putra; Fairuz Dhiya Putri; Muhammad Sufyan Rabbani; Selvy Gita Cahyani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The franchise business trend is growing rapidly, including in the iced tea trade. One of them that is currently viral is the Solo iced tea franchise business. This research examines the widespread trading of solo iced tea franchises from the field and habitus perspective of Pierre Boudieu. In this research, researchers used a qualitative and descriptive approach about the rise of the Solo Ice Tea Business. The author uses case study research with literature study and in-depth interviews. Habitus' perspective shows that people's consumption habits and preferences for local products contribute to the popularity and growth of this franchise. The development of the Es Teh Solo franchise is strongly influenced by the interaction between social structure (Field) and individual disposition (Habitus). The combination of economic, social and cultural capital is the key to success in a competitive market.